Macrophages and neutrophils in ovarian cancer microenvironment - Cheng, Kuang-Chao; Lin, Yu-Hsin; Wu, Dao-Sian; Shih, Ie-Ming; Wang, Tian-Li (Frontiers in Immunology, 2025)
Ovarian cancer (OC) remains one of the most aggressive gynecological malignancies, with a five-year survival rate below 45% despite the recent advances in the introduction of targeted therapy. Moreover, immunotherapy, such as immune checkpoint inhibitors, does not improve the survival of OC patients. Lack of sufficient knowledge in understanding the complexity of the tumor microenvironment likely confers the treatment ineffectiveness. Recently, tumor-associated macrophages (TAMs) and tumor-associated neutrophils (TANs) have garnered research attention as they shape the tumor immune microenvironment, which plays a crucial role in disease progression and treatment response. This article reviews the complex roles of these innate immune cells in OC progression. TAMs represent a significant component of the immune infiltrate in OC, exhibiting considerable functional plasticity and can shift between anti-tumoral (M1) and pro-tumoral (M2) phenotypes. M2-like TAMs typically predominate in the tumor microenvironment, which aids in the development of immune suppression and disease progression. They also contribute to chemoresistance and metastasis; hence, their presence in tumors is associated with a worse prognosis. TANs, like TAMs, exhibit N1/N2 polarization and influence tumor progression through the formation of neutrophil extracellular traps. Understanding the biological interactions between various immune cells and cancer cells may offer new therapeutic opportunities. This review sheds light on the dynamic ecological transformation of the OC tumor microenvironment and highlights the potential of targeting TAM/TAN-mediated processes to improve OC treatment outcomes.